Overall Buckling and Wrinkling of Debonded Sandwich Beams: Finite Element and Experimental Results - Hadi, Bambang K. (Journal of Engineering and Technological Sciences, 2006)
Overall buckling and wrinkling of debonded sandwich beams under compressive loads were analyzed by both finite element and experimental methods. In the finite element method, a quarter and a half models of the specimens were analyzed. It shows that a quarter model is not adequate to analyze buckling of debonded sandwich beams, since it will disregard overall buckling mode that may occur in sandwich beams having compressive loads. At least a half model should be used to analyze buckling of sandwich beams. A finite element program UNA was used extensively to analyze the buckling loads. Experimental buckling of sandwich beams was carried out using a compression testing machine. Two LVDTs were used to measure deflections of the specimen during experimental loading. The loads were measured using load cells available in the machine. Specimens having core thickness of 45 and 75 mm were tested to represent overall and wrinkling modes respectively. The delamination lengths were 20, 60 and 80 mm, which represent 10, 30 and 40% of the beam length. The results show that the differences between experimental and finite element methods were less than 10%. Both overall buckling and wrinkling modes were shown in these specimens.